Sex-specific compensatory model of suicidal ideation: a population-based study (Urban HEART-2) - Fatemeh Rashidi; Keyvan Karimi; Khashayar Danandeh; Abtin Ansari; Mohsen Asadi-Lari; Amir Hossein Memari (BMC, 2024)
Abstract Introduction Suicidal ideations (SI), also known as suicidal thoughts, refer to impulses, desires, and obsessions related to death. Prevalence of suicidal ideation was 14 percent. The current study assumed that identifying the true predictors of SI would allow for a greater understanding of suicide risk. Methods In this cross-sectional population-based study, 17,644 residents aged from 15 to 90 years were selected through a multi-stage sampling method from 22 districts of Tehran. Using hypothesized causal models, the pathways through which various variables influenced the components of SI were identified. Also, the applicability of the compensatory and risk-protective models of resiliency for the prediction of SI was tested by using the interaction multiple regression analyses. Results SI was experienced by 13.44% of the study population. SI was more prevalent with individuals between the ages of 15 to 24. There are no differences between men and women when covariate analysis is used. The significant predictions by anxiety and physical activity (moderate) indicate support for the compensatory model for male and female, while the significant prediction by those indicates support for the risk-protective model for females. Conclusion PA would both lessen the detrimental impact of anxiety on suicidal thoughts and potentially reduce the probability of SI. It's important to develop and evaluate PA-enhancing treatments, especially for woman who are experiencing anxiety.